The effect of injury on whole-plant senescence: an experiment with two root-sprouting Barbarea species - Martínková, Jana; Šmilauer, Petr; Mihulka, Stanislav; Latzel, Vít; Klimešová, Jitka (Annals of botany, 2016)
BACKGROUND AND AIMS: Senescence is the process of losing fitness when growing old, and is shaped by the trade-off between maintenance and reproduction that makes reproduction more unsure and maintenance more costly with age. In repeatedly reproducing plants, reductions in growth and fertility are signs of senescence. Disturbance, however, provides an opportunity to reset the ageing clock and consequently potentially ameliorate senescence. METHODS: To test the effects of disturbance on traits closely related to fitness and thus to senescence, a long-term garden experiment was established with two short-lived perennial congeners,Barbarea vulgaris and Barbarea stricta, that differ in their ability to resprout after injury. In the experiment, five damage treatments were applied to plants in four different phenophases. KEY RESULTS: It was found that damage to the plant body significantly prolonged life span in B. vulgaris but decreased whole-life seed production in both species. High concentration of seed production in one growing season characterized short life spans. Both more severe damage and a more advanced phenological phase at the time of damage caused reproduction to be spread over more than one growing season and equalized per-season seed production. In terms of seed quality, average weight of a single seed decreased and seed germination rate increased with age regardless of damage. CONCLUSIONS: Although disturbance is able to reset the ageing clock of plants, it is so harmful to plant fitness that resprouting serves, at best, only to alleviate slightly the signs of senescence. Thus, in terms of whole-life seed production, injured plants were not more successful than uninjured ones in the two studied species. Indeed, in these species, injury only slightly postponed or decelerated senescence and did not cause effective rejuvenation.
Keywords: Plant Roots; Models, Biological; rozmnožování; Species Specificity; Seeds; Time Factors; Reproduction; kořeny rostlin; velikost těla; Body Size; semena rostlinná; statistické modely; Models, Statistical; klíčení; Germination; druhová specificita; Barbarea; biologické modely; časové faktory